Weed competitive ability of faba bean (Vicia faba), pea (Pisum sativum), and vetch (Vicia sativa) crops under semi-arid conditions - Angeliki PETRAKI; Angeliki KOUSTA; Maria GERAKARI; Eleni ABRAHAM; Demosthenis CHACHALIS (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
Agricultural practices must adapt to address new climatic conditions and the rising global demand for food. Among these practices, cultivating crops resilient to various stresses while maintaining productivity—such as annual legume crops—is essential. This study aims to assess the competitive interactions between legume crops and weeds. Field experiments were conducted using a Randomized Complete Block design with three replicates. Six weed treatments, representing the presence and absence of weeds (utilizing natural weed communities) were applied as the main plots for each of three-grain legumes: pea (Pisum sativum), faba bean (Vicia faba), and vetch (Vicia sativa), under semi-arid Mediterranean conditions. To evaluate the crops' competitive abilities, weed and crop biomass were collected at 3, 6, and 9 weeks after sowing (WAS). Additionally, pod yield was measured for each species to determine crop yield. The results indicated that faba bean exhibited the strongest growth competition, sowing: a) the smallest difference in final (9WAS) biomass between weedy and weed-free treatments compared to peas and vetch (30, 55, 57% reduction, respectively), and b) significant benefits in continuous removal of weeds in peas, vetch as compared to the no-benefits in such treatment in faba beans.  In terms of yield tolerance to weed competition, peas demonstrated the greatest resilience, followed by faba beans and vetch (24, 38, 76% reduction, respectively). The timing of the manifestation of the crops' suppressive abilities varied: in peas and vetch, there was no measurable effect on growth due to the weed competition at the early and medium stages (at 3 and 6WAS) of crop development but only at the late stage (9WAS).  Given the importance of grain legumes and the limited research on their competitive interactions with weeds, further studies are needed to promote more sustainable agricultural practices.